Micromechanical Modeling of Piezo-Magneto-Thermo-Elastic Composite Structures: Part II - Applications - Jothi, Sathiskumar; Georgiades, Tasos; Hadjiloizi, Demetra (My University, 2012)
Two comprehensive micromechanical models for the analysis of piezo-magneto-thermo-elastic smart composite structures with orthotropic constituents are developed and applied to examples of practical importance. Details on the derivations of the aforementioned models are given in Part I of this work. The present paper solves the derived unit cell problems and obtains expressions for such effective coefficients as piezomagnetic, piezoelectric, elastic and many others. Of particular importance are the effective product properties, such as magnetoelectric, pyroelectric and pyromagnetic coefficients which, in general, manifest themselves in the macroscopic composite as a consequence of the interactions of the different constituents but are not exhibited by the constituents themselves as individual entities. The effective coefficients are universal in nature and once determined, can be used to examine a number of boundary value problems associated with a given composite geometry. The present work illustrates the use of the developed models and compares the results obtained with corresponding results stemming from other analytical and/or numerical models. Furthermore, results from the two micromechanical models presented here are also compared with each other. The mathematical model developed in this work can be used in analysis and design to tailor the effective elastic, piezoelectric, piezomagnetic, magnetoelectric etc. coefficients of smart composite structures to meet the design criteria of different engineering applications by a judicious selection of different geometric and/or material parameters of interest.
Keywords: Microelectromechanical systems; Thermoelasticity; Geometry